Lessons learned from Paris and Nice. (30th October 2017) - Noël, S.; François, A.; Le Failler, F.; Charpentier, F.; Baudonnet, T.; Bierling, P.; Djoudi, R.; Pirenne, F.; Killic, S.; Benomar, D.; Corby, J.‐B.; Fabra, C.; et al.
Abstract : On 13 November 2015, between 9:20 pm and 00:20 am, terrorists committed several attacks in Saint‐Denis and the East Parisian districts. These attacks, claimed by the organization Islamic State, constitute the deadliest series of multisite attacks that France has experienced. The stake for the Etablissement Français du Sang (EFS, the French public blood service) was to face the shockwave that propagated throughout the whole establishment from the very minutes following the events, impacting all the processes and stakeholders involved in the transfusion chain, which were challenged by a massive blood donor influx as soon as 14 November 2015. This article covers the impacts of the attacks on immunohaematology and delivery activities as well as the actions that were implemented to ensure sufficient blood supply. Then, the impacts on blood component production are set out. EFS integrated organization and available stocks allowed meeting blood requirements and enabled a strong control of outdating, after unprecedented blood collections during the weeks following 13 November 2015. Lastly, the article presents EFS experience feedback of Paris attacks and of the event that occurred in Nice on 14 July 2016, which helped improve our crisis management pattern with: Specific steps implemented in delivery facilities located in hospitals that were flooded by a large number of victims; An analysis of the postattack donor population; A reflection on optimal organizational schemes to face a donation influx; Actions to leverage the consequences of a 'media wave' that could potentially result in useless, excessive blood collections.